Utilization of browse supplements with varying tannin levels by Ethiopian Menz shee1. Intake, digestibility and live weight changes - Kaitho, R.J.; Umunna, N.N.; Nsahlai, I.V.; Tamminga, S.; Bruchem, J. van (Springer, 1997)
The effect of tannins in browse supplements on intake, digestibility and live weight changes was evaluated using sixty-six male Ethiopian Menz sheep in a 90-day trial. Teff straw (Eragrostis tef) was fed ad libitum (control diet), or supplemented with 190 g dried leaves of six Sesbania sesban accessions with increasing levels of condensed tannin (S1, S2, S3, S4, S5 and S6), lablab (Dolichos lablab), tagasaste (Chamaecytisus palmensis), leucaena (Leucaena leucocephala) and goetzei (Sesbania goetzei), in a completely randomized block design. The condensed tannins were highest in goetzei, S6, S5 and leucaena, intermediate in S4, S3, S2 and S1, and lowest in tagasaste and lablab. The forages differed signfificantly (P<0.05) in their rates of degradation and truly undegradable dry matter. Lablab had lower water solubility and higher (P<0.05) truly undegradable dry matter than the other browse supplements. With increasing tannin levels among Sesbania accessions, there was a significant decrease (P<0.05) in the rate of degradation. Animals supplemented with forage legumes with low condensed tannin levels such as lablab, S1, S2, and S3 had a lower teff straw intake than those on the control diet. The converse was true for those fed with the high tannin supplements such as S4, S5, S6 and goetzei. Supplementation significantly (P<0.05) increased total dry matter intake and live weight gains (LWG). The animals on the control diet lost weight (-1.9 g/kgW0.75), while the supplemented animals gained between 2.9 and 4.4 g/kg W0.75 daily. Leucaena supplementation promoted higher (P<0.05) LWG than lablab, S1 and goetzei. With increasing tannin levels among Sesbania accessions. There was an increase (S1<S2<S3<S4) followed by a decrease (S6>S5>goetzei) in LWG. The digestibilities of total DM and the supplements did not differ significantly (P>0.05) between the diets, although the neutral detergent fibre (NDF) digestibility decreased significantly (P<0.05) with supplementation. The control diet had significantly higher NDF digestibility than the leucaena, S3, S4, S5 and S6 supplemented diets. Results have beneficial attributes at low levels in ruminants. Condensed tannins confer important advantages in ruminant nutrition with respect to the prevention of excessive degradation of protein in the rumen.